Bone mineral density and vitamin K status in children with celiac disease: Is there a relation? - Volkan, Burcu; Fettah, Ali; İşlek, Ali and Kara, Soner Sertan and Kurt, Nezahat and Çayır, Atilla (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: To investigate bone mineral density (BMD) in children with celiac disease (CD) and to evaluate the association between vitamin K levels and osteoporosis. Materials and Methods: Children with CD and age- and sex-matched healthy control subjects were prospectively included in the study. BMD was measured, and serum anti-tissue transglutaminase IgA, ferritin, folate, vitamin B12, 25-hydroxy vitamin D and K2, calcium, phosphate, alkaline phosphatase, and parathormone were assayed in all subjects. Results: Overall, 72 patients (mean age 11.69±3 years, 59.7% female) and 30 healthy subjects (mean age 12.27±2.12 years, 63.3% female) were enrolled. The mean BMD Z score of the celiac group was significantly lower than that of the control group (−1.23±1.07 vs. −0.35±1.04, p=0.001). Vitamin D and K2 values did not differ significantly between the two groups (p>0.05). BMD was positively correlated with vitamin D (r=0.198, p=0.001) and negatively with PTH (r=−0.397, p=0.002). Conclusion: The BMD of celiac patients was lower than that of the control subjects. There was no difference in terms of vitamin D and K2 levels between the two groups. Further studies investigating the level and effect of vitamin K on bone in CD are needed. Cite this article as: Volkan B, Fettah A, İşlek A, Kara SS, Kurt N, Çayır A. Bone mineral density and vitamin K status in children with celiac disease: is there a relation? Turk J Gastroenterol 2018; 29: 215-20.